The role of personal control in the palliative function of system justification among indigenous and non-indigenous Peruvian students / El rol del control personal en la función paliativa de la justificación del sistema entre la población indígena y no indígena de estudiantes peruanos. Issue 1 (2nd January 2019) - Vargas-Salfate, Salvador
Abstract: In this article we propose a mediation model for the association between system justification and psychological well-being (i.e., the palliative function of ideology), based on system justification theory and compensatory control theory. Specifically, we argue that endorsing system-justifying beliefs leads to increased perceived personal control, which in turn predicts higher well-being. We used a convenience sample of students from two Peruvian universities. The results showed that system justification was related to general psychological well-being and personal control. In addition, indigenous students rated lower on system justification, general psychological well-being, self-esteem and personal control. Next, we found that the association between system justification and general psychological well-being was stronger among indigenous students, and this relationship was partially mediated by personal control. In addition, we showed that the mediation model is moderated by ethnicity, so that personal control is a mediator only among non-indigenous participants. We conclude that personal control is a mechanism involved in the palliative function of ideology among this group. Finally, we discuss possible explanations for the mechanisms involved in the palliative function of ideology among low-status individuals.